2022
DOI: 10.3390/ijerph19095089
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on the Mental Well-Being of College Students

Abstract: The COVID-19 pandemic has caused an overall increase in stress and depression in society. The aim of the present research was to evaluate the psychological condition of college students during the COVID-19 pandemic and explore factors influencing their daily functioning. The study focused on four main aspects such as mental well-being, sexuality, concern about financial status, and trust in medical authorities. The study was based on a specially designed survey. The questionnaire was created using Google Forms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 70 publications
0
8
0
1
Order By: Relevance
“…The findings of this study suggest a noteworthy relationship between the perception of high levels of stress, as measured by the USS, and increased perceptions of the pandemic's impact on social relationships among freshmen. The transition to university life is inherently stressful, and the added stressors brought on by the pandemic, such as remote learning, reduced social interactions, and uncertainty, may have compounded these stress levels [52,57]. Consequently, freshmen who have a higher perception of stress may be more inclined to perceive the pandemic as having a detrimental effect on their social relationships.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study suggest a noteworthy relationship between the perception of high levels of stress, as measured by the USS, and increased perceptions of the pandemic's impact on social relationships among freshmen. The transition to university life is inherently stressful, and the added stressors brought on by the pandemic, such as remote learning, reduced social interactions, and uncertainty, may have compounded these stress levels [52,57]. Consequently, freshmen who have a higher perception of stress may be more inclined to perceive the pandemic as having a detrimental effect on their social relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Academic self-efficacy is significantly related to psychological well-being and mental health, since several authors have found that a higher confidence to address academic tasks has a negative relationship with mental health disorders, such as depression, anxiety, and stress (e.g., Tak et al, 2017;Tahmassian & Jalali Moghadam, 2011; Sabouripour et In correspondence to several studies on the prevalence of mental health problems on university students during the COVID-19 pandemic (e.g., Chen & Lucock, 2022;Li et al, 2021;Chang et al, 2021), we found that approximately one third of the sample experienced severe to extremely severe symptoms of depression, anxiety, and stress. In most cases, students faced a disruption on their lives during the pandemic such as the feelings of loneliness due to the social isolation practices, lack of financial resources which increased stress and implied poor nutrition and housing, as well as the need to keep adapting to academic demands (Sauer et al, 2022). As such evidence persists, researchers conclude that there is a strong need for providing mental health care resources to university students, not only by their educational institution (Copeland et al, 2021), but also as a government policy (Chen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This study focused on one protective factor within the academic context, academic self-efficacy, as a potentially protective factor against the three aforementioned mental health conditions during the first year of the COVID-19 pandemic. As shown in the literature, the pandemic itself brought several stressors, and for university students, most of them are related to changes in their academic efforts and well-being (e.g., Oliveira Carvalho et al, 2021;Sauer et al, 2022;Werner et al, 2021). For this reason, we hypothesize that higher academic self-efficacy in university students will be associated with less severe symptoms of depression, anxiety, and stress.…”
Section: Introductionmentioning
confidence: 92%
“…As early as February 2020, psychiatrists and researchers were warning of the impact of lockdowns and other responses on depression, anxiety, fear, panic attacks, suicidality, and other severe mental health problems, among both patients and health workers [ 43 , 44 ]. Studies around the world have found alarming rates of depression and stress on particular groups, such as caregivers of persons with dementia in Hong Kong (nearly two-thirds suffered from probable depression) [ 45 ], college students in Poland (over one-third reported poor mental health requiring treatment) [ 46 ], college students in China (nearly one-quarter reported mild-to-severe anxiety) [ 47 ], and young adults in Saudi Arabia (over 90% reported mild-to-severe symptoms of mental health disease) [ 48 ].…”
Section: Covid-19 Pandemic Responsementioning
confidence: 99%